Influence of operational and economic factors on the optimal design of an electric vehicle battery cooling system - Gundran, Julius Ezra M. (Animo Repository, 2020)
Electric vehicles are a leading alternative to traditional vehicles. However, high expenditure on battery replacement due to rapid capacity loss limits their market penetration. Given that the high temperatures reached during operation greatly contribute to capacity loss, battery cooling systems are often necessary to extend battery life. In designing a cooling system, lifetime cost is a crucial consideration as both capital expenditure and battery replacement cost savings are associated with the system. To extend the prior initial study, this study investigates the influence of various factors on the economically optimal design. Similar to the initial study, the investigated case is that of a typical electric jeepney in Manila, Philippines. Existing models for the electrothermal and aging behavior of the battery, thermal behavior of the cooling system, and capital costs of the cooling system components are linked to form a system simulation. The simulation, implemented in Simulink is coupled with a genetic algorithm implementation in MATLAB to generate the optimal cooling system design. As with the initial study, air and phase change material are the cooling media considered. Given their significant expected influence on the optimal design, the following factors are investigated: drive cycle, ambient temperatures, and component capital costs. The results of this study agree with the preliminary study. The optimization results do not favor air cooling in any case investigated; none of the cases justify its high capital and operating costs. Phase change material (PCM) cooling is also unfavored in all cases, save for that using the US06 drive cycle, showing that only extreme temperature rise due to high current draw can justify investment in PCM cooling. Although previous studies have found that lowering battery temperature extends battery life, this study reveals that the capital and operating costs of battery cooling systems are still a hurdle to be overcome. © 2020 Institute of Physics Publishing. All rights reserved.